Dissertatio inauguralis of Serbian poet Laza Kostić: 'De legibus serbicis Stephani Uros Dusan' - Bujuklić Žika (Anali Pravnog Fakulteta u Beogradu)
On the basis of the archival material he recently discovered, the author provides the answer to the question he asked in his recently published paper: 'Defense of doctorate by Serbian poet Laza Kostić in Pest in 1866: Dissertatio or Theses?' By analyzing the previously unknown contents of Kostić's doctoral diploma and original records from his doctoral examinations at the Royal University in Pest (1864-1866), the author concludes that Laza Kostić was awarded the title of 'Doctor of General Law', both civil and canonical (doctor universi iuris, utriusque iuris), on the basis of defending the work of a smaller volume 'Theses e(x) scientiis juridicis et politicis', but also by the presentation of dissertatio inauguralis called 'De legibus serbicis Stephani Uros Dusan'. The author believes that this information significantly complements our knowledge of the study of Dušan's legislation in the mid-nineteenth century and enables us to better understand the overall extent of Serbian cultural elite in Hungary at that time.